Kualitas Audit: Pengaruh Karakteristik Perusahaan dan Tata Kelola Perusahaan - Dewi, Cynthia; Anita, Anita (Faculty of Economics, Universitas Internasional Batam, 2019)
The purpose of this study is to quantify the effect of company?s characteristics and corporate governance towards audit quality in companies listed in the Indonesia Stock Exchange (IDX). Independent board, board size, foreign ownership, ownership concentration, profitability as well as institutional ownership is used in this study. The amount of 618 companies listed on the Indonesia Stock Exchange during the period of 2013-2017 is used in this study. Purposive sampling method is used in the study. Financial statements of company that was published (www.idx.co.id) used as the sample of this study. The calibration of data which was obtained with binary logistic regression will be process using the program of SPSS version 25.0. This research shows that board size, foreign ownership and profitability proved to have a positive and significant relation on audit quality. This research also shows that institutional ownership does not have a significant relationship on audit quality while board independence has a negative relationship towards audit quality.